2015
DOI: 10.1103/physrevb.92.104413
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetism atT>500Kin the layered hexagonal ruthenateSrRu2O6

Abstract: We report an experimental and computational study of magnetic and electronic properties of the layered Ru(V) oxide SrRu 2 O 6 (hexagonal, P3 ̅ 1m), which shows antiferromagnetic order with a Néel temperature of 563(2) K, among the highest for 4d oxides. Magnetic order occurs both within edge-shared octahedral sheets and between layers and is accompanied by anisotropic thermal expansivity that implies strong magnetoelastic coupling of Ru(V) centers.Electrical transport measurements using focused ion beam induce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 45 publications
(63 reference statements)
3
34
0
Order By: Relevance
“…While the nominal Ru valence of 5+ in the octahedral crystal field dictates three electrons in the 4d t 2g orbitals, a neutron powder diffraction study revealed a local magnetic moment of 1.4 µ B per Ru atom [14], which is significantly lower than 3 µ B expected for the high-spin S = 3/2 configuration. We synthesized hexagonal single crystals with typical diameter of ∼ 50 µm ( Fig.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…While the nominal Ru valence of 5+ in the octahedral crystal field dictates three electrons in the 4d t 2g orbitals, a neutron powder diffraction study revealed a local magnetic moment of 1.4 µ B per Ru atom [14], which is significantly lower than 3 µ B expected for the high-spin S = 3/2 configuration. We synthesized hexagonal single crystals with typical diameter of ∼ 50 µm ( Fig.…”
mentioning
confidence: 86%
“…Here we introduce a resonant inelastic x-ray scattering (RIXS) [10,11] technique capable of probing collective modes in microcrystals of 4d-electron materials. We present a comprehensive set of data on spin waves and spin-state transitions in the honeycomb antiferromagnet SrRu 2 O 6 [12], which possesses an unusually high Néel temperature [13][14][15][16][17][18]. The new RIXS method provides fresh insight into the unconventional magnetism of SrRu 2 O 6 , and enables momentum-resolved spectroscopy of a large class of 4d transition-metal compounds.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the physics of this structural family is much richer and there are many more instabilities that interfere with the Kitaev interactions, in particular under pressure. Indeed, Li 2 RuO 3 is nonmagnetic and strongly dimerized at ambient pressure [13][14][15], while SrRu 2 O 6 is an ultra-high-temperature antiferromagnet [16,17], despite having the same planar geometry, and shows no bond disproportionation.Many factors control the competition between Kitaev physics, magnetism, and dimerization [18] in A 2 M O 3 honeycomb networks, such as the number of transition metal M d-electrons, the strength of spin-orbit coupling, the strength of correlation effects and Hund's rule coupling, or the ionic radii of the buffer element A. In this context it is particularly instructive to compare α-Li 2 IrO 3 with Li 2 RuO 3 , which contains the same buffer element (Li).…”
mentioning
confidence: 99%